Long-term gains from longer school days - Patricio Domínguez; Krista Ruffini (Inter-American Development Bank (IDB), 2020)
This paper examines whether additional time in elementary and secondary school affects economic well-being in adulthood. This paper explores a large-scale reform that increased the Chilean school day by 30 percent between 1997 and 2010, with access to longer school days varying by cohort and city. Both sources of variation are leveraged and it is found that full-day schooling increases educational attainment, delays childbearing, and increases earnings in young adulthood. The nature of these benefits is consistent with more time in school facilitating human capital accumulation, and the results show that large scale investments in public education can generate long-term improvements in economic well-being.
Keywords: I26; I25; J24; H52; 330; Economics of education; returns to education; full-day schooling; long-term investments